Postoperative hepatitis B virus reactivation and its impact on survival in HBV-related hepatocellular carcinoma patients undergoing conversion therapy with interventional therapy combined with tyrosine kinase inhibitors and immune checkpoint inhibitors - Xu, Shaowei; Pang, Qingqing; Wei, Meng; Liu, Danxi; Yuan, Du; Bai, Tao; Wang, Xiaobo; Tang, Zhihong; Wu, Feixiang (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThis study aimed to investigate hepatitis B virus (HBV) reactivation and its impact on postoperative survival in patients with HBV-related hepatocellular carcinoma (HCC) who underwent conversion therapy. The therapeutic regimen consisted of interventional procedures (hepatic artery infusion chemotherapy [HAIC] and/or transarterial chemoembolization [TACE]) combined with tyrosine kinase inhibitors (TKIs) and immune checkpoint inhibitors (ICIs).MethodsA retrospective analysis was performed at a single institution involving 91 patients who had initially unresectable HCC linked to the hepatitis B virus. These patients achieved resectability following conversion therapy and subsequently underwent surgical tumor removal. Logistic regression identified risk factors for HBV reactivation (HBVr). Kaplan-Meier survival analysis and log-rank tests assessed survival differences. Cox proportional hazards regression was used to identify independent predictors of progression-free survival (PFS) and overall survival (OS).ResultsIn our cohort, HBVr occurred in 17 patients (18.7%), all of whom received antiviral therapy. The incidence of HBVr was 16.7% (14/84) in patients with detectable baseline HBV DNA and 42.9% (3/7) in those with undetectable levels. Baseline HBV DNA ≥2000 IU/ml was identified as an independent protective factor against HBVr (OR 0.090, 95% CI 0.015–0.532; P = 0.008). The median PFS was significantly shorter in the reactivation group than in the non-reactivation group (12.1 months [95% CI 5.5–18.7] vs. 29.2 months [95% CI 23.6–34.7]; P < 0.001). However, no significant difference was observed in median OS between the two groups (not reached vs. 45.6 months [95% CI 41.7–49.5]; P = 0.117).ConclusionHBVr represents a potential complication in subjects receiving hepatectomy for hepatitis B virus associated HCC following conversion therapy involving interventional therapies combined with TKIs and ICIs. Patients experiencing HBVr exhibited significantly shorter progression-free survival compared to those without reactivation. Therefore, prophylactic antiviral therapy and meticulous HBV DNA monitoring are warranted during both conversion therapy and the perioperative period.